A study on Nikkei-225 futures index - Ang, San Yeow (2013)
The collapse of Barings, one of England’s oldest banks, received a lot ofmedia attention and aroused much interests. The huge loss on the trading ofNikkei- 225 Futures contracts by Mr Nick Leeson, sent a shock wave through the financial world. This put the Nikkei-225 Futures contracts in the limelight for quite a while. It was this incident that motivated us to research into the Nikkei- 225 Futures Index.